Mathematics
         
语言:中文    Language:English
On line Solution of Monovariate Equation:
    Input any unary equation directly, and then click the "Next" button to obtain the solution of the equation.
    It supports equations that contain mathematical functions.
    Current location:Equations > Monovariate Equation > The history of univariate equation calculation > Answer

    Overview: 1 questions will be solved this time.Among them
           ☆1 equations

[ 1/1 Equation]
    Work: Find the solution of equation 4[20(t+2)+30t]+25*3t+30*3t+(t+2+0.75)*6*20 = 500t+400 .
    Question type: Equation
    Solution:Original question:
     4(20( t + 2) + 30 t ) + 25 × 3 t + 30 × 3 t + ( t + 2 +
3
4
) × 6 × 20 = 500 t + 400
     Left side of the equation = 4(20( t + 2) + 30 t ) + 75 t + 90 t + ( t + 2 +
3
4
) × 120
                                             = 4(20( t + 2) + 30 t ) + 165 t + ( t + 2 +
3
4
) × 120
    The equation is transformed into :
     4(20( t + 2) + 30 t ) + 165 t + ( t + 2 +
3
4
) × 120 = 500 t + 400
    Remove the bracket on the left of the equation:
     Left side of the equation = 4 × 20( t + 2) + 4 × 30 t + 165 t + ( t + 2 +
3
4
) × 120
                                             = 80( t + 2) + 120 t + 165 t + ( t + 2 +
3
4
) × 120
                                             = 80( t + 2) + 285 t + ( t + 2 +
3
4
) × 120
                                             = 80 t + 80 × 2 + 285 t + ( t + 2 +
3
4
) × 120
                                             = 80 t + 160 + 285 t + ( t + 2 +
3
4
) × 120
                                             = 365 t + 160 + ( t + 2 +
3
4
) × 120
                                             = 365 t + 160 + t × 120 + 2 × 120 +
3
4
× 120
                                             = 365 t + 160 + t × 120 + 240 + 90
                                             = 485 t + 490
    The equation is transformed into :
     485 t + 490 = 500 t + 400

    Transposition :
     485 t 500 t = 400490

    Combine the items on the left of the equation:
      - 15 t = 400490

    Combine the items on the right of the equation:
      - 15 t = - 90

    By shifting the terms and changing the symbols on toth sides of the equation, we obtain :
     90 = 15 t

    If the left side of the equation is equal to the right side, then the right side must also be equal to the left side, that is :
     15 t = 90

    The coefficient of the unknown number is reduced to 1 :
      t = 90 ÷ 15
        = 90 ×
1
15
        = 6 × 1

    We obtained :
      t = 6
    This is the solution of the equation.



Your problem has not been solved here? Please go to the Hot Problems section!





  New addition:Lenders ToolBox module(Specific location:Math OP > Lenders ToolBox ),welcome。